A role for 2-Cys peroxiredoxins in facilitating cytosolic protein thiol oxidation - Stöcker, Sarah; Maurer, Michael; Ruppert, Thomas; Dick, Tobias P. (Nature chemical biology, 2018)
Hydrogen peroxide (H2O2) acts as a signaling messenger by triggering the reversible oxidation of redox-regulated proteins. It remains unclear how proteins can be oxidized by signaling levels of H2O2 in the presence of peroxiredoxins, which are highly efficient peroxide scavengers. Here we show that the rapid formation of disulfide bonds in cytosolic proteins is enabled, rather than competed, by cytosolic 2-Cys peroxiredoxins. Under the conditions tested, the combined deletion or depletion of cytosolic peroxiredoxins broadly frustrated H2O2-dependent protein thiol oxidation, which is the exact opposite of what would be predicted based on the assumption that H2O2 oxidizes proteins directly. We find that peroxiredoxins enable rapid and sensitive protein thiol oxidation by relaying H2O2-derived oxidizing equivalents to other proteins. Although these findings do not rule out the existence of Prx-independent H2O2 signaling mechanisms, they suggest a broader role for peroxiredoxins as sensors and transmitters of H2O2 signals than hitherto recognized.